Effect temperature in chemical sensing using triple stage microring resonator - Mohamad, Azam; Bahadoran, Mahdi; Aziz, Safwan; Chaudary, Kashif; Jalil, Muhammad Arif; Ali, Jalil; Yupapin, Preecha (My University, 2015)
The split-step Fourier technique is used to study the effect of temperature in triple stage microring resonating sensor (TSMRRS). The optical bright soliton beam is used as the probe pulse into the TSMRRS and the effect of temperature variations on various concentrations of glucose in deionize water is investigated. The detection of glucose is measured by intensity variations of output signals from through and drop ports of TSMRRS. The temperature variations cause an exact intensity reduction of glucose concentration in deionize water when the temperature increased by 1 °C. The performance of TSMRRS glucose sensor is improved for temperature range similar with standard room temperature which shows that TSMRRS is suitable candidate for chemical sensing application.
Keywords: Optical sensor; Optical soliton; Temperature sensor; Triple stage ring resonator